Structured Discussion Strategy in Islamic Religious Education: Enhancing Students’ Learning Motivation and Conceptual Understanding in Vocational Schools - Kusmiati Kusmiati; Masita Masita; Muslimin Muslimin (Journal of Islamic Education Students (JIES), 2026)
Islamic Religious Education (PAI) is often perceived by students as a theoretical subject that emphasizes memorization rather than meaningful understanding, which may reduce students’ learning motivation. Therefore, innovative learning strategies are required to create a more engaging and participatory classroom environment. This study aims to analyze the influence of structured discussion strategies on students’ learning motivation, perceptions toward PAI, and conceptual understanding in Islamic Religious Education classes at State Vocational High School 1 Kota Bima. This research employed a qualitative approach using observation, interviews, and documentation to obtain comprehensive data regarding classroom dynamics and learning processes. The findings indicate that the implementation of structured discussion strategies significantly increased students’ participation, confidence, and engagement during the learning process. Students’ perceptions of PAI shifted from viewing it as a purely theoretical subject to recognizing it as a relevant moral and ethical framework applicable to everyday life and future professional contexts. In addition, students demonstrated deeper conceptual understanding by moving from memorization-based learning toward more analytical and contextual comprehension. These findings suggest that structured discussion strategies can foster a more dialogical, participatory, and meaningful learning environment in vocational secondary schools. However, this study was limited to a single school context and a relatively small number of participants. Future research is recommended to involve broader samples and employ mixed-method approaches to further examine the effectiveness of structured discussion strategies in different educational settings.